The Effect of Military Ethics and Motivation on The National Commitment of The Indonesian Military - Bambang Heru Sukmadi; Ma'ruf Akbar; Billy Tunas; Zulvia Khalid (Program Studi S3 Ilmu Manajemen, 2019)
This research is aimed to explore and find out the effect of military ethics and motivation on the national commitment of the soldiers of the Indonesian Army. The research is conducted on the soldiers in the rank of non-commissioned and enlisted soldiers at one of the Indonesian Army units in Jakarta. The data is collected with the survey method on the sample that comprises of 83 respondents which are taken with a simple random sampling technique. The data is analyzed quantitatively from an organizational behavior perspective with the Path Analysis technique utilizing SPSS 22 software. The test of normality and linearity of each regression between variables results in a normal distribution of residual and linearly related. The results of this research show that (1) military ethics has a positively direct effect on national commitment; (2) military ethics has a positively direct effect on motivation; (3) motivation has a positively direct effect on national commitment; (4) military ethics has an indirect effect on national commitment through motivation.